Variants of R-weakly commuting mappings and common fixed point theorems in intuitionistic fuzzy metric spaces - CHAUHAN, SUNNY; KUTUKCU, SERVET; DHIMAN, NEERAJ; KUMAR, SUNEEL (Kuwait Journal of Science, 2014)
In this paper, we utilize the notion of common limit range property with variants of -weakly commuting mappings and obtain some common fixed point theorems in intuitionistic fuzzy metric spaces. We give some illustrative examples which support our results. Consequently a host of common fixed theorems are generalized and improved.